The vulnerability of European regional labour markets to job automation: the role of agglomeration externalities. Issue 10 (2nd November 2021) - Crowley, Frank; Doran, Justin; McCann, Philip
ABSTRACT: Automation is expected to have strong implications for labour-saving technologies. We calculate the proportion of jobs at high risk of automation across European regions using data from the 2018 Labour Force Survey (LFS). We examine the relationship between regional vulnerability to job automation, specialization, related (and unrelated) variety and agglomeration. The results indicate that regions at low vulnerability to job automation benefit from unrelated variety and high population density. Regions with higher proportions of clerical support workers, craft and related trade workers, and plant and machine operators and assemblers are likely to face greater disruption.